The use of povidone-iodine and hydrogen peroxide mixture as an adjunct to non-surgical treatment of slight to moderate chronic periodontitis - Mohammed Y. Al-Saeed; Nadir Babay (Elsevier, 2009)
Objective: The aim of this study was to evaluate the clinical effects of the adjunctive use of povidone-iodine with or without hydrogen peroxide as coolant and disinfectant during ultrasonic scaling and root planing in the treatment of chronic periodontitis. Materials and methods: Sixteen patients initially participated in the study. Thirteen patients (8 males and 5 females) completed the 3-month follow-up period. Their mean (±SD) age was 42.92 ± 7.55 years. In each experimental subject, the mouth was split into four quadrants. A randomly selected quadrant was chosen to receive one of the three treatment group modalities which were: Group 1 - ultrasonic scaling and root planing plus irrigation with 1% povidone-iodine and 3.0% hydrogen peroxide mixture; Group 2 - ultrasonic scaling and root planing plus irrigation with 1% povidone-iodine; Group 3 - ultrasonic scaling and root planing plus irrigation with normal saline. The fourth quadrant served as a control group. Results: At the 3-month evaluation, there was no significant difference between the three treatment groups in terms of probing depth reduction, clinical attachment gain, gingival recession increase, reduction in the bleeding upon probing or plaque score reduction (P > 0.05). However, the three treatment groups had statistically significant higher mean reduction in the probing depth, gain in the clinical attachment level and reduction in the bleeding upon probing than the control group (P < 0.05). Conclusion: There were no added benefits of using a mixture of povidone-iodine and hydrogen peroxide or povidone-iodine as disinfectants during ultrasonic scaling and root planing in the treatment of chronic periodontitis. Keywords: Povidone-iodine, Hydrogen peroxide, Periodontitis